Simple strategies for effective PowerPoint presentations - Canavor, Natalie 1942- (FT Press Delivers, 2010)
This is the eBook version of the printed book. If the print book includes a CD-ROM, this content is not included within the eBook version. This Element is an excerpt from The Truth About the New Rules of Business Writing (9780137153152) by Natalie Canavor and Claire Meirowitz. Available in print and digital formats. How to make sure your PowerPoint presentations ignite people-instead of sedating them!The speaker strides to the podium ... turns down the lights ... presses Advance ... and slide by slide, his speech splashes across the screen so everyone can stare at the written words and hear an oral version at the same time. Later you get a handout that's identical to the slides. A multisensory experience? No, just a boring one.
Keywords: Microsoft PowerPoint (Computer file); Business communication; Business presentations; Communication dans l'entreprise; Présentations (Affaires); LANGUAGE ARTS & DISCIPLINES; Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES; Rhetoric; REFERENCE; Writing Skills; Journalism & Communications; Communication & Mass Media